HUBUNGAN ANTARA POLA PENGASUHAN KESEHATAN REPRODUKSI ORANG TUA DENGAN PERILAKU KESEHATAN REPRODUKSI ANAK USIA 10 DAN 11 TAHUN DI KOTA MOJOKERTO (Dalam Rangka Pencegahan Kekerasan Seksual Pada Anak) - DHONNA ANGGRENI, 101414153038 (2016)
The parenting patterns in delivering reproductive health education is very influential towards the growth and development of children specifically for their reproductive health problems. The objective of this research is to analyze the relationship between reproductive health parenting patterns and reproductive health behavior of children in order to prevent their sexual abuse in Mojokerto City. The applied research design is crosssectional. This research is done at SDN (Public Elementary School) Meri 1 and SDN Kranggan 2 in Mojokerto City in June 2016. The population of this research is the entire students of the fourth and fifth grades along with their parents. The sample of this research is 103 people and its taking technique applies simple random sampling. The independent variable of this research is reproductive health parenting patterns, and the dependent variable of this research is reproductive health behavior of children in order to prevent their sexual abuse. The data collection is done by distributing questionaires to respondents. The data analysis is accomplished by applying Chi Square and Exact Fisher test. The result of the research shows the existence of the relationship between reproductive health parenting patterns and reproductive health knowledge of children in Mojokerto City, the existence of the relationship between reproductive health parenting patterns and reproductive health behavior of children in Mojokerto City, the existence of the relationship between reproductive health parenting patterns and reproductive health measure of children in order to prevent their sexual abuse in Mojokerto City. Reproductive health education done by parents towards children can increase their awarness and confidence, so it will influence formed behavior at last. Children will try to protect their reproductive health and themselves in order to prevent sexual abuse. Parents should start giving reproductive health education to their children in accordance with their needs as early as possible.